The female of the species - McGinnis, Mindy (Katherine Tegen Books, an imprint of HarperCollinsPublishers, 2016)
Three years after her sister's murderer walked free and Alex Craft skillfully achieves her vengeance without detection, she begins to form a friendship with the preacher's daughter and draws the attention of popular Jack Fisher, until the dark side of Alex finds its way out.